Faktor-Faktor yang Mempengaruhi Penerimaan PPH Final Usaha Mikro Kecil Menengah (UMKM) Pada Kantor Pelayanan Pajak Pratama Pematang Siantar - Zulia Hanum; Rafika Fadila Daulay; Sri Endang Rahayu; Hastina Febriaty (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
This study aims to examine and analyze the effect of taxpayers, investment and GRDP on MSME final income tax receipts. MSME Final PPh receipts are one of the final income taxes, namely as stipulated in Law no. 36 of 2008 concerning Income Tax as regulated in article 4 paragraph (2). This study uses a quantitative approach with an associative research design. The population in this study is the MSME tax receipts report at the Pematang Siantar Primary Tax Service and the sample in this study is MSME actors at the Pematang Siantar Primary Tax Service Office. The data analysis technique uses multiple linear regression analysis with the help of SPSS 20 software. The results of this partial study are that taxpayers have an effect on MSME Final Income Tax Receipts at KPP Pematang Siantar, Investments have an effect on MSME Final Income Tax Receipts at KPP Pematang Siantar and GRDP has an effect on Revenue MSME Final Income Tax at KPP Pematang Siantar, while the results of this simultaneous study are Taxpayers, Investment and GRDP have an effect on MSME Final Income Tax Receipts at KPP Pematang Siantar.